Cenografia Urbana no Auto do Círio: a cidade de Belém como palco de celebração - BESSA, Gabrielle Aboul Hosn (2024)
The Auto do Círio is an artistic tribute to Nossa Senhora de Nazaré, in the form of a procession through the streets of Belém, creating unique and personal experiences, promoting a cultural and artistic communion in the city. The spectacle involves devotion, faith, and diversity, transcending religious barriers. The procession is marked by collective construction, a city and its people, valuing artistic expression and cultural heritage. The intrinsic relationship between the Auto do Círio and the city is explored, highlighting urban scenography as a visual language that enriches its identity. The research was based on qualitative methodology with a descriptive basis in the experience report, in addition to the search for theorists in the areas of theater and scenography. This study contributes significantly to the understanding of the interaction between scenography and theater, emphasizing the relationship of the Cidade Velha neighborhood and the Auto do Círio as a spectacle that goes beyond the street procession, transforming the city into a stage of celebration, tradition, and art.